Predictors of COVID-19 Vaccine Uptake Among Healthcare Workers in Kiambu County, Kenya - Edmond Muthee Waweru; Wanyoro A. Karanja; Osborn Tembu (Journal of Immunization, 2025)
Coronavirus Disease 2019 (COVID-19) placed significant pressure on global health systems, necessitating rapid and widespread immunization, especially among healthcare workers (HCWs). Despite being prioritized in immunization programs, variations in vaccine uptake among HCWs have been reported across different settings. This study aimed to investigate the predictors of COVID-19 vaccine uptake among HCWs in Kiambu County, Kenya. An analytical cross-sectional study design was employed, involving 112 HCWs sampled using stratified random sampling from Level 2 to Level 5 healthcare facilities. Data were collected through a pre-tested and validated 18-item questionnaire and analyzed using SPSS version 29.0. Statistical methods included descriptive analysis, chi-square tests, logistic regression, and ANOVA. The overall COVID-19 vaccine uptake was 88.9%. Significant predictors of uptake included age (p = 0.048), cadre (p = 0.015), and facility level (p = 0.031). Knowledge of COVID-19 vaccines emerged as the strongest predictor, with HCWs demonstrating good-to-excellent knowledge being 14.97 times more likely to be vaccinated (p < 0.001). Confidence in vaccine safety and effectiveness was also significantly associated with uptake (p < 0.001). Uptake was highest in Level 5 hospitals and lowest in dispensaries. The study reveals high vaccine uptake among HCWs in Kiambu County, but disparities persist due to individual and systemic factors. Strengthening vaccine education, institutional support, and deploying mobile vaccine education units in lower-level facilities could help close these gaps, offering practical strategies for improving HCW vaccine coverage in Kenya and other low- and middle-income countries.
Keywords: COVID-19